Study on Adipocytes as Sensors of Lipid Transport through Caco-2/HT29-MTX Intestinal Barrier Rescued from Cancer Phenotype by Oleic Acid - Emmanuelle Berger; Alain Géloën (Recent Research Advances in Biology Vol. 11, 2021)
Gastrointestinal epithelium is the unique route for nutrients and for many pharmaceuticals to enter the body. The present study aimed to analyze precisely whether co-culture of two colon cancer cell lines, mucus-producing cells HT29-MTX and enterocyte-like Caco-2 cells, ameliorates differentiation into a functional in vitro intestinal barrier model. Experimental validations were performed in real-time experiments, immunochemistry, and gene expression analyses on Caco-2 versus co-cultures of Caco-2 and HT29-MTX (10%) cells. Partial maintenance of cancer-cell phenotype in differentiated Caco-2 cells was confirmed and fatty acids merged as potential regulators of cancer signaling pathways. HT29-MTX cells induced morphological changes in Caco-2 cells, slightly increased their proliferation rate and profoundly modified gene transcription of phenotype markers, fatty acid receptors, intracellular transporters, and lipid droplet components as well as functional responses to oleic acid. In vitro, enterocyte phenotype was partially rescued by co-culture of cancer cells with goblet cells and completed through oleic acid interaction with signaling pathways dysregulated in cancer cells. Such a reconstructed gastrointestinal epithelium was tested on lipid transport. Adipose tissue function in the regulation of lipemia is highly dependent on intestinal absorption of nutrients. Therefore we developed and validated an in vitro multiculture model allowing to measure intestinal absorption using adipocytes as lipid sensors. Oleic acid (OA) was pre-absorbed onto the reconstructed intestinal barrier. Optimized experimental conditions for co-culture with intestinal barriers were obtained with partially differentiated 3T3L1-MBX adipocytes sensing up to 5 µM OA in solution or 40 µM OA pre-absorbed by Caco2/HT29-MTX intestinal barriers. Metabolism including glycemia and insulinemia greatly influenced the ability to accumulate TG in adipocytes. The present study demonstrates a much better functionality for fatty acid uptake and release in Caco2/HT29-MTX versus Caco-2 intestinal barriers. Taken together these results open new opportunities to study in vitro lipid transfer between intestinal barriers and either adipocytes or hepatocytes.